A path of possibilities. Artistic experiences in a paediatric oncology ward - Bengoechea Menéndez, Camino; Moreira Sánchez, Carina (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2014)
In this paper we present a series of art projects developed in the paediatric oncology unit of Madrid Montepríncipe Hospital. In it, their professionals work in a coordinated manner by adapting the protocol for the child in order to individualize treatment, highlighting the creative process as an important part in the comprehensive care of the patient. Presentation of case studies, methodologies and procedures used.